Effect of Poverty and Economic Growth on Indonesia Human Development Index - Heppi Syofya (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Human development is defined as a process for enlarging people's choices, the Human Development Index is a benchmark of human development achievement based on a number of basic components of the quality of life of IPM is built through a basic three-dimensional approach that is 1). Dimensions of longevity and healthy life (a long and healthy life), 2). Knowledge and 3). Decent standard living, through the improvement of these three indicators is expected to increase the quality of human life due to individual heterogeneity, geographical disparity and societal conditions vary so that the level of income is no longer the main benchmark in calculating the success rate of development and success, poverty is a condition that is below the minimum standard of needs, both for food and non-food items called the poverty line or poverty threshold, the poverty rate and economic growth have a significant effect on the Index Human Development in Indonesia and economic growth have an influence on the Human Development Index in Indonesia